2014
DOI: 10.1021/ar500249k
|View full text |Cite
|
Sign up to set email alerts
|

Light-Directing Chiral Liquid Crystal Nanostructures: From 1D to 3D

Abstract: Endowing external, remote, and dynamic control to self-organized superstructures with desired functionalities is a principal driving force in the bottom-up nanofabrication of molecular devices. Light-driven chiral molecular switches or motors in liquid crystal (LC) media capable of self-organizing into optically tunable one-dimensional (1D) and three-dimensional (3D) superstructures represent such an elegant system. As a consequence, photoresponsive cholesteric LCs (CLCs), i.e., self-organized 1D helical super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
233
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(236 citation statements)
references
References 44 publications
0
233
0
3
Order By: Relevance
“…It is also difficult to envisage the fabrication of complex, extended 3D networks or geometries using this technique. In other disciplines, a range of selfassembly and chemical methods have resulted in great success in the fabrication of 3D nano/microstructures, including chiral liquid crystal structures [11,12] and hybrid 3D graphene/gold nanoparticle structures [13]. In addition, the manipulation of droplets upon surfaces via magnetic guiding and three-phase contact lines has been shown to be a powerful method to produce 3D microstructures in a number of geometries, including magnetic inks [14], CdTe quantum dots [15], silver nanoparticles [15], and manganese chloride salts [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is also difficult to envisage the fabrication of complex, extended 3D networks or geometries using this technique. In other disciplines, a range of selfassembly and chemical methods have resulted in great success in the fabrication of 3D nano/microstructures, including chiral liquid crystal structures [11,12] and hybrid 3D graphene/gold nanoparticle structures [13]. In addition, the manipulation of droplets upon surfaces via magnetic guiding and three-phase contact lines has been shown to be a powerful method to produce 3D microstructures in a number of geometries, including magnetic inks [14], CdTe quantum dots [15], silver nanoparticles [15], and manganese chloride salts [15].…”
Section: Introductionmentioning
confidence: 99%
“…[6] It has been shown that plasmonic nanostructures forming 1D [7] elements, 2D metasurfaces, [8][9][10] and 3D metamaterials [11] can exhibit linear chiral response due to their own, intrinsic chirality. Also semiconductor nanostructures can exhibit chiral features.…”
mentioning
confidence: 99%
“…[124][125][126] Red shifts in the reflection band upon illuminating azobenzene doped blue phases with light have also been demonstrated in the visible region. [127,128] Furthermore, there are also number of other organic based 2D and 3D photonic materials which reflect narrow bandwidths of light, mostly in the visible region. [129,130] These materials could be adjusted to interact in the infrared region.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%